Cancellation Of The Deed Of Land Sale And Purchase Agreement Due To One Of The Parties Defaulting, Viewed From The Aspects Of Legal Certainty And The Value Of Justice - Imraatus Sholichah, Charis (Universitas Islam Malang, 2023)
Abstract: The Land Sale and Purchase Agreement (PPJB) contains the rights and obligations of the parties who made it, so that if the matters agreed upon in the Sale and Purchase Agreement (PPJB) deed are violated or not fulfilled by the parties who made it, then this can be said to have been default occurs. It is possible to cancel the Sales and Purchase Agreement (PPJB) unilaterally by one of the parties or with the agreement of both parties. The land sale and purchase agreement (PPJB) can also be canceled by a court decision. The method used in this research is normative juridical research, as for the formulation of the problem, what are the consequences of canceling the deed of land sale and purchase agreement due to one of the parties defaulting in terms of legal certainty and the value of justice. What are the procedures for canceling the deed of land sale and purchase agreement if one of the parties defaults? The results of this research analysis are that if viewed from the perspective of legal certainty, the binding sale and purchase agreement aims to obtain legal certainty regarding the land to be purchased which binds both parties to carry out the performance, because the buyer is in default, the seller can request the cancellation of the PPJB to the court. . The conditions for cancellation are deemed to be contained in agreements that have reciprocity, when one party defaults, so that the agreement will return to the way it was before the agreement was entered into, the seller must return what has been deposited by the buyer. Apart from that, as a result of the court's decision to annul the deed, the deed will be relegated to a private deed if the drafting does not comply with statutory regulations. The procedure for canceling the Deed of Land Sale and Purchase Agreement if one of the parties is in default is to submit a request to the court by means of a notary who makes a deed of the land sale and purchase agreement which is forwarded to the court regarding the cancellation of the agreement so that with a final court decision there is certainty. and justice for the parties. Keywords: Cancellation of Deed of Agreement, Sale and Purchase Agreement, Default